The conjugal dictatorship of Ferdinand and Imelda Marcos - Mijares, Primitivo (Bughaw, 2017)
"This book reports on the best laid plans that paved the way to the Philippines' dark history: the imposition of martial law in 1972 and the schemes that built and held its infrastructure. Drawing data from his work as Marcos's media adviser before his defection in 1975, Primitivo Mijares exposes the massive corruption and military abuses under the regime, which has left the nation in ruins. Forty years after its first publication, the book, in this revised and annotated edition, reminds Filipinos of their past that remains a present threat."--Back cover.